Combined Effects of Temperature and Salinity on the Pharmacokinetics of Florfenicol in Nile Tilapia (Oreochromis niloticus) Reared in Brackish Water - Rairat, Tirawat; Liu, Yi-Kai; Hsu, Julia Chu-Nin; Hsieh, Chia-Yu; Chuchird, Niti; Chou, Chi-Chung (Frontiers in Veterinary Science, 2022)
Prudent antimicrobial use requires knowledge of pharmacokinetics (PK) in a specific fish species which in turn depends on water temperature and salinity. Although the influence of each individual factor is known, the combined effect is less clear. The objective of the current study was to investigate the effect of temperature and salinity concurrently on the PK of florfenicol (FF) in Nile tilapia reared in brackish water. Twenty-eight fish were divided into four groups and kept at one of the two temperatures (24 vs 32°C) and two salinity levels (5 vs 15 ppt). The FF was administered at a single dose of 15 mg/kg body weight via oral gavage. The serum concentrations were analyzed by HPLC method and the PK parameters were analyzed by a 2-compartmental model. The result revealed that at 32°C, the elimination half-lives (t1/2β), time to reach the peak concentration (Tmax), area under the serum concentration-time curve (AUC), and mean residence time (MRT) were significantly decreased, while the clearance relative to bioavailability (CL/F) significantly increased compared to those of 24°C. The extents of these PK changes were similar at the two salinity levels. On the contrary, increasing the salinity from 5 to 15 ppt at a given temperature level produced no significant change in the PK behavior. Our finding indicated that only water temperature, but not salinity, is the major determinant factor governing the FF fate in the fish body.